ChemInform Abstract: How Phenyl Makes a Difference: Mechanistic Insights into the Ruthenium(II)‐Catalyzed Isomerization of Allylic Alcohols. Issue 26 (1st July 2014) - Manzini, Simone; Poater, Albert; Nelson, David J.; Cavallo, Luigi; Nolan, Steven P.
Abstract A Ru‐3‐phenylindenyl complex is shown to be highly active for the isomerization of allylic alcohols (I) and (III) into the corresponding ketones (II) and (IV).